Effects of Precursor and Deposition Conditions on Prevention of Bacterial Biofilm Growth on Chlorinated Plasma Polymers. Issue 6 (11th January 2016) - Michl, Thomas D.; Coad, Bryan R.; Hüsler, Amanda; Valentin, Jules D. P.; Vasilev, Krasimir; Griesser, Hans J.
Abstract : In this work, we aimed to understand the key properties that confer antibacterial activity to chlorinated plasma polymers, by investigating plasma polymers deposited from a series of chlorinated precursor molecules and also investigating the effect of plasma conditions. Results revealed that only precursors with a Cl/C ratio ≥1.5 generate effective antibacterial coatings, whereas the coating thickness is irrelevant. Furthermore there is a "sweet spot" in process conditions to generate coatings with optimal antimicrobial activity. Lastly, we investigated the release of chlorinated fragments and attenuation of the surface‐active antibacterial properties of the chlorinated plasma polymers by overcoating them with a perfluorinated plasma polymer. Abstract : The ability of chlorinated plasma polymers to prevent biofilm formation by Staphylococcus epidermidis was found to vary markedly . Effective coatings were obtained when the precursor molecule has a Cl/C ratio of ≥1.5, but plasma deposition conditions also play a strong role. Prevention of biofilm growth was maintained upon soaking in water. The mechanism of action appears to arise from mobile oligomeric components of the plasma polymers, which accumulate at the film/aqueous interface and destabilize bacterial membranes.